Efficiency and regulation in the sanitation sector in Brazil - Ronaldo Serôa da Motta; Ajax Reynaldo Bello Moreira (Institute for Applied Economic Research (ipea), 2015)
Regulation in the sanitation sector in Brazil is facing a great deal of debate regarding the government level in which conceding authority should reside and how private operators can fulfill social objectives. The main objective of this study is to show that these issues are not the crucial barriers to the development of the sector when one looks at the productivity performance of the operators. Therefore, we elaborate a detailed analysis of the productivity performance of the current structure of the sanitation sector in Brazil. In doing so, we are able to analyze how jurisdiction of operators as well as the nature of the management, either private or public, has affected performance of the current operators. Moreover, we investigate how the absence of tariff regulation has dissipated efficiencies and allowed the practice of monopolistic tariffs.
Keywords: L11; L51; L95; 330